Crisis and Contemporary Poetry
XII, 260 p.
Keywords: What are the means available to poetry to address crisis and how can both poets and critics meet the conflicts and challenges they face? This collection of essays addresses poetic and critical responses to the various crises encountered by contemporary writers and our society, from the Holocaust to the ecological crisis.